2023
DOI: 10.1177/21677026231186803
|View full text |Cite
|
Sign up to set email alerts
|

Integrating “Lumpers” Versus “Splitters” Perspectives: Toward a Hierarchical Dimensional Taxonomy of Eating Disorders From Clinician Ratings

Kelsie T. Forbush,
Yiyang Chen,
Po-Yi Chen
et al.

Abstract: In this study, we describe a hierarchical dimensional model of eating-disorder (ED) classification based on the Hierarchical Taxonomy of Psychopathology. Participants were community-recruited adults with an ED ( N = 252; 81.9% female). We used a modified version of Goldberg’s method, which involved sequentially extracting latent factors using exploratory structural equation modeling, resulting in a 10-factor hierarchical-dimensional model. Dimensions predicted 92.4% and 58.7% of the variance in recovery outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 74 publications
1
1
0
Order By: Relevance
“…We retained body dissatisfaction in the PCA because whether it was included did not change the three-factor PCA structure and did not change the statistical significance of results in subsequent analyses. Results of the PCA were consistent with our past research in sample with clinically significant EDs (Forbush et al, 2023), where binge eating, purging, and body dissatisfaction also formed a higherorder factor. Negative attitudes toward obesity was included as a separate predictor in the regression models.…”
Section: Principal Component Analysis Of Ed Measuressupporting
confidence: 89%
“…We retained body dissatisfaction in the PCA because whether it was included did not change the three-factor PCA structure and did not change the statistical significance of results in subsequent analyses. Results of the PCA were consistent with our past research in sample with clinically significant EDs (Forbush et al, 2023), where binge eating, purging, and body dissatisfaction also formed a higherorder factor. Negative attitudes toward obesity was included as a separate predictor in the regression models.…”
Section: Principal Component Analysis Of Ed Measuressupporting
confidence: 89%
“…HiTOP offers an ideal framework for initial assessment and routine outcomes measurement to help clinicians select tailored modules and inform decisions about when to "pivot" to different modules. For example, Forbush et al (2023) found that HiTOP measures prospectively predicted more variance in relevant outcomes than all other traditional disorder-specific indicators, a finding that is consistent with several retrospective studies (see Kotov et al, 2022, for a review). These results have led to an innovative clinical trial in which Forbush et al are using weekly HiTOP assessments in conjunction with machine learning to provide clinicians with a "stop-light tool" that generates a visual depiction of when clients are at risk for poor outcomes (ClinicalTrials.gov NCT05190926).…”
Section: The Utility Of Hitop In Measurement-based Caresupporting
confidence: 68%
“…Despite the shift in terminology, the same issues remain, and these diagnoses provide limited information for treatment planning or prognosis (Forbush et al, 2023;Kotov et al, 2022).…”
Section: Challenges Of Traditional Diagnostic Systemsmentioning
confidence: 99%